Air-sea gas transfer in high Arctic fjords - Andersson, Andreas; Falck, E.; Sjöblom, A.; Kljun, N.; Sahlee, E.; Omar, A. M.; Rutgersson, A. (Geophysical Research Letters, 2017)
In Arctic fjords and high-latitude seas, strong surface cooling dominates during a large part of the year, generating water-side convection (w(*w)) and enhanced turbulence in the water. These regions are key areas for the global carbon cycle; thus, a correct description of their air-sea gas exchange is crucial. CO2 data were measured via the eddy covariance technique in marine Arctic conditions and reveal that water-side convection has a major impact on the gas transfer velocity. This is observed even at wind speeds as high as 9ms(-1), where convective motions are generally thought to be suppressed by wind-driven turbulence. The enhanced air-sea transfer of CO2 caused by water-side convection nearly doubled the CO2 uptake; after scaled to open-sea conditions the contribution from w(*w) to the CO2 flux remained as high as 34%. This phenomenon is expected to be highly important for the total carbon uptake in marine Arctic areas.